Analysis of the Needs of Fungi Material Teaching Modules at Muhammadiyah 1 High School, Air Saleh Regency Banyuasin - Umami, Riza; Astriani, Meli; Habisukan, Ummi Hiras (Bioilmi: Jurnal Pendidikan, 2024)
Biology education at the senior high school level has an important role in providing students with an understanding of basic concepts regarding aspects of life, one of which is fungi. Fungi are one of the important topics in biology and have an important role in the ecosystem. The purpose of this study was to determine the needs of schools in creating teaching modules about fungi for grade X that are in accordance with the curriculum. The research method used is descriptive qualitative. The results of the study showed that the curriculum implemented at SMA Muhammadiyah 1 Air Saleh uses the Independent Curriculum, students prefer the way teachers teach using Student Worksheets (LKPD) media, with the Project Based Learning (PjBL) model. Practicum was chosen as a solution to solve problems given by teachers. The conclusion of this study is that schools have implemented the latest curriculum by analyzing student needs and teachers prefer learning using Student Worksheets (LKPD) and solving problems by creating project-based teaching modules.